Advanced ultra‐high molecular weight polyethylene/antioxidant‐functionalized carbon nanotubes nanocomposites with improved thermo‐oxidative resistance. Issue 33 (20th May 2015) - Dintcheva, Nadka Tzankova; Arrigo, Rossella; Gambarotti, Cristian; Carroccio, Sabrina; Coiai, Serena; Filippone, Giovanni
ABSTRACT Multiwalled carbon nanotubes (CNTs) functionalized with hindered phenol moieties are dispersed in ultra‐high molecular weight polyethylene (UHMWPE), and the stabilizing action of the antioxidant (AO) functionalized CNTs (AO‐f‐CNTs) is studied through a combination of rheological and spectroscopic (FT‐IR) analyses. The effectiveness of two alternative compounding methods, namely hot compaction (HC) and melt mixing (MM), is compared. The combination of high temperature and mechanical stress experienced during MM brings about noticeable degradation phenomena of the matrix already in the course of the compounding step. Differently, the milder conditions of the HC process preserve the stability of the polymer, making this method preferable when dealing with highly viscous matrices. In addition, HC guarantees a better CNT dispersion, allowing for the maximization of the stabilizing action of the AO grafted on the nanotubes. As a result, the HC samples exhibit improved thermo‐oxidative resistance despite the very low amount of AO grafted onto the CNTs. Besides demonstrating the effectiveness of our AO‐f‐CNTs as stabilizers for polymer matrices, our results prove that CNTs can serve as a support on which grafting specific functional molecules to be dispersed in a host polymer matrix. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42420.